Practice in industry training in fish culture - Ferrer, Armando R. (Diliman, Quezon City College of Fisheries, University of the Philippines, 1956)
The six-month practice-in-industry training is a requirement for graduation. This institution required this training to teach and help his student to reach the high technicality, knowledge and to gain more experience in the propagation of bangos and other aquatic products cultivated for human use and consumption. Because of the vast aquatic resources in the Philippine inland, waters fishing is generally considers our third basic industry. The most important is to know the theoretical and practical side of fish culture to help our people to eat fresh fish in lowest cost.
Keywords: Fish-culture.